2021
DOI: 10.1093/sw/swab052
|View full text |Cite
|
Sign up to set email alerts
|

Needs of Children and Families during Spring 2020 COVID-19 School Closures: Findings from a National Survey

Abstract: Despite extensive reports during the COVID-19 pandemic of the academic challenges facing students, and the effects of online learning on academic achievements, we have little information regarding the needs and difficulties of K–12 students and their families from a social work perspective. The present article shares findings from a nationwide survey of 1,275 school social workers (SSWs) reporting on their clients—schools, children, and families—during the spring 2020 COVID-19 school closures. SSWs indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, the majority of this research focuses on child protection practice and community‐based social work. In the US, SSW researchers have begun to investigate SSW practice during the COVID era (e.g., Childs et al, 2022; Daftary et al, 2021; Kelly et al, 2021; Watson et al, 2022), but there remains a limited understanding of how COVID‐19 has shaped family engagement in US schools and the role of SSWers in school–family relationships. We addressed this critical gap in the literature by exploring SSWers' practices related to family engagement and their attitudes towards and perspectives regarding those practices during the early stages of the COVID‐19 pandemic and as the pandemic continued past the initial national quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of this research focuses on child protection practice and community‐based social work. In the US, SSW researchers have begun to investigate SSW practice during the COVID era (e.g., Childs et al, 2022; Daftary et al, 2021; Kelly et al, 2021; Watson et al, 2022), but there remains a limited understanding of how COVID‐19 has shaped family engagement in US schools and the role of SSWers in school–family relationships. We addressed this critical gap in the literature by exploring SSWers' practices related to family engagement and their attitudes towards and perspectives regarding those practices during the early stages of the COVID‐19 pandemic and as the pandemic continued past the initial national quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…In a February 2021 survey of school district leaders, 77% reported that their students had fallen behind in their social‐emotional development compared to two years prior 26 . While telling of needs from the lens of practitioners and teachers, few studies capture student perspectives on how their socioemotional skills and competencies were affected during the COVID‐19 pandemic 27,28 . Capturing the student perspective is crucial and advantageous for informing the development of student‐centered interventions promoting social and emotional well‐being and skills 10,29 .…”
Section: Covid‐19 School Closures and Socioemotional Well‐beingmentioning
confidence: 99%
“…Capturing the student perspective is crucial and advantageous for informing the development of student‐centered interventions promoting social and emotional well‐being and skills 10,29 . We also know little about their nonacademic needs beyond those reported by school‐based practitioners who voiced concerns about student well‐being regarding housing, food, and health care needs 28,30 …”
Section: Covid‐19 School Closures and Socioemotional Well‐beingmentioning
confidence: 99%
See 2 more Smart Citations